EDUCATIONAL HYPERMEDIA ON PERIPHERAL VENIPUNCTURE: THE PERSPECTIVE OF STUDENTS OF NURSING - Natasha Marques Frota; Lívia Moreira Barros; Amanda de Fátima Alves da Costa; Zélia Maria de Sousa Araújo Santos; Joselany Áfio Caetano (Universidade Federal do Paraná, 2014)
This descriptive qualitative study aimed to identify the opinion of students in relation to the use of educational hypermedia on Peripheral Venipuncture in the teaching of nursing. Interviews were held with 12 students of nursing from a public university, during the first semester of 2013. The interviews, through content analysis, allowed the identification of the nuclei of meaning and categorization, and gave rise to four categories: Influence of the hypermedia course on the learning, Educational technology as support for proximate teaching, Hypermedia's relationship with professional practice, and Difficulties in access. Hypermedia presented positive results, as the majority of the students reported that the material helped in the learning and led to autonomy and interactivity at the time of studying. However, some mentioned difficulty in accessing the hypermedia, mainly related to the server used. Thus, hypermedia was shown to be a valid tool for use, as it promoted learning and awoke the interest and curiosity of the students